2021
DOI: 10.3390/en14040965
|View full text |Cite
|
Sign up to set email alerts
|

Research on a Comprehensive Maintenance Optimization Strategy for an Offshore Wind Farm

Abstract: Offshore wind is considered a crucial part in the future energy supply. However, influenced by weather conditions, the maintenance of offshore wind turbine system (OWTs) equipment is challenged by poor accessibility and serious failure consequences. It is necessary to study the optimized strategy of comprehensive maintenance for offshore wind farms, with consideration of the influences of incomplete equipment maintenance, weather accessibility and economic relevance. In this paper, a Monte Carlo algorithm-impr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Novel maintenance strategies have been constantly proposed to increase the reliability of turbines and reduce cost. [5][6][7] Opportunistic maintenance is one of the emerging concepts, which groups different types of maintenance activities of multiple turbines together to reduce costs. [8][9][10][11][12] Life cycle cost is an important measure used to assess the efficiency of turbine maintenance strategies.…”
Section: Operation and Maintenance Of Offshore Wind Farmsmentioning
confidence: 99%
See 1 more Smart Citation
“…Novel maintenance strategies have been constantly proposed to increase the reliability of turbines and reduce cost. [5][6][7] Opportunistic maintenance is one of the emerging concepts, which groups different types of maintenance activities of multiple turbines together to reduce costs. [8][9][10][11][12] Life cycle cost is an important measure used to assess the efficiency of turbine maintenance strategies.…”
Section: Operation and Maintenance Of Offshore Wind Farmsmentioning
confidence: 99%
“…A variety of decision support models have shown that O&M have a great influence on the economy of wind projects. Novel maintenance strategies have been constantly proposed to increase the reliability of turbines and reduce cost 5–7 . Opportunistic maintenance is one of the emerging concepts, which groups different types of maintenance activities of multiple turbines together to reduce costs 8–12 .…”
Section: Introductionmentioning
confidence: 99%
“…The selection of an appropriate maintenance strategy plays a pivotal role in the normal functioning of wind farms. Optimal maintenance strategies depend on various factors, including energy costs, required reliability levels, weather conditions, availability of skilled technical personnel, and the accessibility of crew transport vehicles [35][36][37]. Maintenance strategies may vary across different power plants based on factors such as the type, size, and number of wind turbines, required reliability, and other maintenance standards [38].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Selecting an appropriate wind farm location must be specific to a particular administrative region, which involves restrictions balance and trade-offs [4][5][6]. The location of a wind farm is very important to the feasibility of wind turbine investment, and it is also related to environmental impacts such as wildlife and socio-economic factors.…”
Section: Introductionmentioning
confidence: 99%